2023
DOI: 10.1186/s12879-023-08362-1
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus screening in community pharmacies: results on feasibility from a Swiss pilot

Abstract: Background Hepatitis C virus (HCV) infections are a public health burden worldwide and often go undetected until sequelae develop. Offering HCV screening for the different vulnerable populations in community pharmacies could help prevent further undetected HCV infections. This pilot aimed to assess the feasibility and pharmacist acceptance of HCV rapid antibody saliva testing in community pharmacies. Methods A structured pharmaceutical care interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Among the single arm intervention studies, pharmacists or pharmacy staff conducted testing within the pharmacy in all studies, with the exception of two: one with testing conducted by in-reach nurses; the other by in-reach phlebotomists ( Table 2 ). Test uptake was 11.2%, 43 33.3% 47 and 57.1% 50 in the three single arm studies with available data.…”
Section: Resultsmentioning
confidence: 82%
“…Among the single arm intervention studies, pharmacists or pharmacy staff conducted testing within the pharmacy in all studies, with the exception of two: one with testing conducted by in-reach nurses; the other by in-reach phlebotomists ( Table 2 ). Test uptake was 11.2%, 43 33.3% 47 and 57.1% 50 in the three single arm studies with available data.…”
Section: Resultsmentioning
confidence: 82%
“…37 Patients' negative views and experiences about testing in community pharmacies were also identified as a barrier to screening. 49 Brewer et al 36 noted that 28% of patients were not willing to receive testing at community pharmacies. The lack of adequate information provision by pharmacists was one of the barriers that were constantly mentioned for not wanting to do screening in community pharmacies.…”
Section: Barriers To Hepatitis Screening In Community Pharmaciesmentioning
confidence: 99%
“…Moreover offering HCV care in pharmacies has been shown to increase screening and treatment uptake [46,66], so pharmacies should be involved in the implementation of a national screening campaign. A recent publication has shown that HCV Ab screening using rapid tests with saliva is feasible in Swiss community pharmacies [67].…”
Section: Clinical Implication Of the Studymentioning
confidence: 99%